2021
DOI: 10.1097/txd.0000000000001220
|View full text |Cite
|
Sign up to set email alerts
|

Comanagement With Nephrologist Care Is Associated With Fewer Cardiovascular Events Among Liver Transplant Recipients With Chronic Kidney Disease

Abstract: Supplemental Digital Content is available in the text.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

3
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 25 publications
3
5
0
Order By: Relevance
“…[13] Similarly, the same group has shown that LT recipients with or at risk of CKD also present a lower probability of CVE if comanaged with a nephrologist. [36] Together with our results, these studies highlight the relevance of establishing multidisciplinary, patient-oriented teams to achieve better CVR control after LT.…”
Section: Discussionsupporting
confidence: 78%
“…[13] Similarly, the same group has shown that LT recipients with or at risk of CKD also present a lower probability of CVE if comanaged with a nephrologist. [36] Together with our results, these studies highlight the relevance of establishing multidisciplinary, patient-oriented teams to achieve better CVR control after LT.…”
Section: Discussionsupporting
confidence: 78%
“…One of the remarkable findings in our study was the low rate of follow-up by the nephrology department despite CKD. In the literature, joint follow-up with nephrology has been associated with fewer cardiovascular events in liver transplant patients [12] and better management both before and after liver [13], heart, and lung [14] transplantation.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, in a recent work, we failed to demonstrate that BP < 130/80 mm Hg was associated with a reduction in CVEs or mortality in LTRs. [1] We also showed that very few (range 3%-14%) LTRs achieve BP < 130/80 mm Hg within the first 6 years after LT. [4] In the current study, data were inadequate to fully assess the potentially deleterious effects of excessive BP lowering or the effects of white coat hypertension (i.e., elevated office BP but out-of-office normotension) or masked hypertension (i.e., office BP in the normotensive range but out-of-office hypertension), which are associated with adverse cardiac risk in the general population. These issues can only be addressed through a rigorous prospective study using medication reconciliation and with the addition of out-of-office BP monitoring, which notably is now recommended by current BP clinical practice guidelines.…”
mentioning
confidence: 88%